2011
DOI: 10.1007/s12008-011-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Water jet incremental sheet metal forming: pressure distribution analysis

Abstract: Incremental Sheet Metal Forming (ISMF) is a very flexible technology for fast prototyping and small batch production of sheet metal parts. This contribution deals with an innovative variant of ISMF, where instead of a rigid tool a Water Jet (WJ) is used as the main tool. Such a process can be addressed as Water Jet Incremental Sheet Metal Forming (WJISMF). The main aim of this paper is to present the technological window for WJISMF and characterize the attributes of the WJ used as the main tool. A Finite Eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…With tests from small distances it was found that for averaged nozzle design efficiency factor Á w can be greater than 0.75 (Sajn et al, 2008). As a first assumption in this study, Á w has been considered equal to 1 and thus, the overpressure on the impacted surface P s considered as uniform and equal to the nozzle overpressure P n .…”
Section: Modelling Of the Mechanical Effectmentioning
confidence: 93%
See 1 more Smart Citation
“…With tests from small distances it was found that for averaged nozzle design efficiency factor Á w can be greater than 0.75 (Sajn et al, 2008). As a first assumption in this study, Á w has been considered equal to 1 and thus, the overpressure on the impacted surface P s considered as uniform and equal to the nozzle overpressure P n .…”
Section: Modelling Of the Mechanical Effectmentioning
confidence: 93%
“…In the literature, experimental and numerical studies on high speed water jet impact on plane surface (Sajn et al, 2008) showed that overpressure in stagnation point on the surface P s can be calculated from Eq. (4):…”
Section: Modelling Of the Mechanical Effectmentioning
confidence: 99%
“…The deformation of the aluminium sheet was analysed by a plane strain theory and it is concluded that the WJ can be used instead of the rigid tools to form the sheets [6]. Jurisevic et al illustrated the pressure and velocity pro les of WJ using two-dimensional nite-element simulation [7][8]. In addition, they introduced laminated supporting tools to increase the accuracy of the WJIF process.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the forming accuracy, Jurisevic et al [14] introduced a laminated tool to support the sheet in the ISF-WJ process, which resulted in forming time reduction and part quality improvement. Aiming to derive the technological window of water jet sheet forming process, Sajn et al [15] carried out numerical modeling and finite element simulation to obtain pressure and velocity distributions, by considering turbulent fluid flow through nozzle and water jet impact on a flat rigid surface. Numerical results were in good agreement with those obtained experimentally to provide an insight of the influence of water jet pressure and water jet nozzle diameter on the process.…”
Section: Introductionmentioning
confidence: 99%